An acoustic analysis of Pahari oral vowels - Khan, Abdul Qadir (Lingua Posnaniensis, 2014)
The aim of the current study is to present an acoustic account of the twelve oral vowels of Pahari by analyzing their formant pattern (F1 and F2) and duration. T o achieve this aim, an experiment was conducted. T em native speakers of Pahari participated in the study and were given a list of 12 oral vowels in CVC context for recording, where V is the target vowel. T he recorded material was analyzed by using Praat software. T he spectral analysis (F1 and F2) show that Pahari has four close, six mid and two open vowels. T he results also show that in term of duration these vowels occur in the form of long-short pairs that differ significantly quantatively (vowel duration).The study further exhibits that the short vowels are centralized as compared to their long counterpart